Did Winston Churchill suffer a myocardial infarction in the White House at Christmas 1941?. (December 2017) - Vale, J Allister; Scadding, John W
Summary: While staying in the White House over Christmas 1941, Churchill developed chest pain on trying to open a window in his bedroom. Sir Charles Wilson, his personal physician, diagnosed a 'heart attack' (myocardial infarction). Wilson, for political and personal reasons, decided not to inform his patient of the diagnosis or obtain assistance from US medical colleagues. On Churchill's return to London, Wilson sought a second opinion from Dr John Parkinson who did not support the diagnosis of coronary thrombosis (myocardial infarction) and reassured Churchill accordingly.